Crescimento e esporulação de duas espécies de arthrobotrys corda em diferentes meios de cultura e dois ambientes - Soares, Pedro Luiz Martins [UNESP]; de Holanda Nozaki, Márcia [UNESP]; Barbosa, Bruno Flávio F. [UNESP]; dos Santos, Jaime Maia [UNESP]; Barbosa, José Carlos [UNESP] (My University, 2009)
The researches on the biological control of nematodes with nematophagous fungi has been intensified in recent years. The knowledge of the ecological conditions for the growth and sporulation of these fungi is a prerequisite for attainment of pure cultures needed to attend the demand for formulation of these organisms. With the objective to evaluate the micelial growth and sporulation of Arthrobotrys musiformis and A. oligospora in two environments (B.O.D at 25 ± 1°C and the environment of the Laboratory), 20 cultures media prepared with common materials found in the communities and industrialized media such as mycological agar, PDA and CMA were evaluated. The media were tested in Petri dishes, being the micelial growth of the fungi evaluated daily, during six days. The measured sporulation at the end of the experiment was done by estimation of the number of conidia/Petri dish. The experiment was carried out in a random design following a factorial arrangement of 20 × 2 × 2, corresponding to 20 media, two fungi and two environments, with five replicates. The variance analysis of the data evidenced significant statistical difference by the F Test, at 1% probability, among media × fungi × environment interaction. Fifty percent of the tested media provided the adequate micelial growth of A. musiformis and there was no statistical difference among them, namely: cassava meal (FM), sweet starch (PD), corn meal agar (CMA), oat in fine flakes (AFF), agar-water + dextrose (AA+D), mycological agar (AM), potato dextrose agar (BDA), meal of maize (FMI), flour of wheat (FT) and wheat for kibble (TK). In relation to A. oligospora, 75% of the tested media promoted the maximum growth of the fungus, which are: AFF, AM, FM, PD, CMA, AA+D, BDA, FT, TK, the water from the decoction of rice (AAZ), rice in grains (AZG), triturated rice (AZT), thread flour (FR), oats flour (FA), oats in thick flakes (AFG) and flour of maize (FU). In relation to the sporulation the media that had better role for A. musiformis, in decreasing order, were: FR, TK, AFG, BDA, FA, AFF, AM, FMI, AZT and FM, varying between 1,01 × 106 and 1,4 × 104 conidia/Petri dish. For the A. oligospora sporulation, the CMA medium provided the maximum level with an estimated average of 5,7 × 106 conidia/Petri dish. In the general, the best media for the micelial growth and sporulation of A. musiformis had also been the best for A. oligospora. However, some that had been the best for the A. oligospora did not had been efficient for the micelial growth or the sporulation of A. musiformis, indicating that the isolate of A. musiformis in case is more demanding than that A. oligospora one. The evidences from the study indicate that, in Jaboticabal, Sao Paulo state, the growth and the sporulation of these fungi do not demand special chambers. Some adaptations of an environment at the laboratory, enough to obliterate the light are sufficient.
Growth and sporulation of two species of Arthrobotrys corda in different culture media and two environments
Keywords: Biological control; Biological control agents; Biological control trap fungi; Fungi; In vitro cultivation; Nematophagous